The critical period of aluminum stress on soybean root growth - Danner Sagala; Eka Suzanna; Prihanani Prihanani (Universitas Prof. Dr. Hazairin SH, 2020)
Aluminum is prevalent in soils of tidal swamps. Soybean is known to be very sensitive to aluminum stress and so when tidal swamps are converted to soybean cropland, considerable effort and expense are required to overcome Al toxicity in soybean roots. It is therefore necessary to determine at what time in early development soybeans can best endure aluminum stress and identify aluminum-tolerant cultivars. This study was conducted by testing the impact of aluminum exposure on three soybean cultivars (Tanggamus, Karasumame, and M652) (relative to no-exposure controls) at four time periods at 10, 20, and 30 days after planting. No significant effect of aluminum on root growth in the first five days after exposure was observed, but the toxic effects became evident after soybeans had been exposed to aluminum for 10 days. Soybean seedlings that experienced aluminum stress earliest (at 10 days after planting) were more negatively impacted by Al exposure than seedlings exposed later (e.g., 30 days after planting). Root growths of the three cultivars we tested in this study were all detrimentally impacted by aluminum exposure. However, the M652 cultivar was the most sensitive to aluminum exposure. We conclude that the critical threshold period for soybean root growth to succumb to aluminum stress is within the first 30 days after planting, whereas the tolerance to aluminum stress occurs only during the first 10 days of exposure.